Peculiarities of linguistic and cultural adaptation of Indian students at higher educational institutions of Ukraine in the intercultural communication context. - Куплевацька, Л. О.; Манівська, Т. Є. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2017)
National peculiar properties of linguistic and cultural adaptation to the learning process of the Indian English speaking students, ways of achievements of successful intercultural communication on the level “student – teacher” at Russian / Ukrainian (as a foreign language) classes have been analyzed in the article. Modern researches of foreign students’ adaptation with the help of different sciences such as General and Social Psychology, Ethnic Psychology, Sociology, Language Teaching Methods and others have been also analyzed. The most studied types of adaptation have been named, complexity and multi-dimensionality of this research have been underlined. Actual definitions of the main terminology and concepts, which operate in this research: linguistic and cultural adaptation, intercultural communication, cultural shock, acculturation stress, have been represented. Modern assessments of Indian foreign students’ acculturation, given by Ukrainian researchers, made in the context of acculturation peculiarities analysis of the students from the South-Eastern region, have been suggested. They allow assigning the peculiar properties of Indian students’ acculturation. Classification of foreign cultures, provided by modern sociologists, from the point of view of chronemics has been examined. It helps to point the peculiarities of Indian students. Similarities and differences which improve linguistic and cultural adaptation and on the contrary to cause acculturation stress have been highlighted by the way of comparison of the learning process in higher schools of Ukraine and India. Some communicative features of the learning process from the point of view of kinetics, proxemics, takesics, chronemics, that prevent the successful acculturation of the Indian students have been called and commented. The reasons and two-pronged nature of acculturation stress of the Indian students have been analyzed. Some methodological decisions to achieve success in linguistic and cultural adaptation in the context of intercultural communication have been examined.